Hubungan Perilaku Hidup Bersih dan Sehat Terhadap Otitis Media Supuratif Kronik (OMSK) - Mai Rista Nila Sari; Mukhlis Imanto (Majority, 2020)
Chronic suppurative otitis media is a chronic infection in the middle ear with perforation of the tympanic membrane and secretions from the middle ear or intermittent. Watery or thick secretions, clear or pus. Chronic suppurative otitis media is a complication of acute otitis media with perforation of the tympanic membrane more than 2 months and discharge, which if not treatment properly will increase the disease progression. The risk factors for the incidence of otitis media are reliable, especially in the nasopharynx and eustachian tube. Risk factors of chronic suppurative otitis media is host factors, infectious factors, environmental factors, sociodemographic factors, lack of patient knowledge about the disease and patient behavior in daily life. Results of Basic Health Research (Riskesdas) The prevalence of Clean and Healthy Life Style in Indonesian 2011 was still low at 38.7%, compared to the National target until 2013 of 65.0%. This paper aims to determine the relationship between clean and healthy life style with chronic suppurative otitis media.